Study the Synergistic Effect of AgNPs with Antibiotics on Klebsiella Pneumoniae Isolates Which Diagnosed by Molecular Methods - Sura Saadoun Khalaf; Hanaa Abdellatif Yassin (Institute of Medico-legal Publications Pvt Ltd, 2021)
The current study was conducted to study the synergistic effect of AgNPs with anti-biotics on Klebsiellapneumonia isolates, where 50 samples were collected from different pathological conditions (wounds - burns- urine - ear - and excretion) on the Maconkey Agar . To the Klebsiella , it was diagnosed microscopicallyand biochemically and was also diagnosed by the Vitek2 device, whose results were identical with thebiochemical diagnosis, and the isolates were also subjected to molecular diagnosis for confirmation byusing the PCR technique based on the diagnostic gene 16SrRNA, which is characterized by being good,stable and low heterogeneity for a long time in the bacterial type Ten types of antibiotics were selectedand immersed in silver nanoparticles At a concentration of 20Mm, a test was conducted for the synergybetween the silver nanoparticles AgNPs and the antagonists towards 12 isolates of Klebsiella bacteria, asthey were applied to Muller-Hunton medium and after they dried up, the anti-saturated tablets were fixedwith a silver particle solution, and after the expiration of the incubation period, the diameter of the inhibitionarea around the tablets was measured in mm According to the standard results, the results of the statisticalanalysis showed that the interaction of silver nanoparticles with the antibiotics had a significant effect onincreasing the sensitivity of the isolates towards the synergistic antagonists, as the general rate of inhibitiondiameters of the antagonists (Impenem, Gentamicin, Amikacin Ciprofloxacillin) was (32.59, 21.6, 18.98,36.18), respectively. , This activity is due to the ability of the nanoparticles to bind to the surface of thebacterial cell The binding causes structural damage and changes such as permeability, which facilitates theentry of the antagonist into the cell and thus its death. As for the synergies with the antagonists Tetracycline,Vancomycin, Erythromycin did not show efficacy in the direction of Klebsiella isolates did not give goodresults of synergy as it has a weak effect towards negative bacteria and it is as a non-synergistic antagonistbecause it does not It has effective binding sites for silver nanoparticles.